2013
DOI: 10.3724/sp.j.1249.2013.05441
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of micro-blog inter-city social interactions in China

Abstract: Video question answering aims at answering a question about the video content by reasoning the alignment semantics within them. However, since relying heavily on human instructions, i.e., annotations or priors, current contrastive learningbased VideoQA methods remains challenging to perform fine-grained visual-linguistic alignments. In this work, we innovatively resort to game theory, which can simulate complicated relationships among multiple players with specific interaction strategies, e.g., video, question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 105 publications
0
4
0
Order By: Relevance
“…Such connections can be derived using transportation and human travel data (Liu, Andris, and Ratti 2010;Phithakkitnukoon et al 2011), or telecommunications data (Gao et al 2013), but these data are difficult to obtain due to privacy and security concerns. Social media account follower data have therefore been used to analyze topological features and to map the spatial distribution of inter-city social interactions in China (Li et al 2013). Data of this type can also be challenging to work with, because user status updates visible on social media are rarely updated, making it difficult to measure the impact of HSR.…”
Section: Spatial Relatedness In the Big Data Eramentioning
confidence: 99%
“…Such connections can be derived using transportation and human travel data (Liu, Andris, and Ratti 2010;Phithakkitnukoon et al 2011), or telecommunications data (Gao et al 2013), but these data are difficult to obtain due to privacy and security concerns. Social media account follower data have therefore been used to analyze topological features and to map the spatial distribution of inter-city social interactions in China (Li et al 2013). Data of this type can also be challenging to work with, because user status updates visible on social media are rarely updated, making it difficult to measure the impact of HSR.…”
Section: Spatial Relatedness In the Big Data Eramentioning
confidence: 99%
“…The Herfindahl-Hirschman index can be used to describe the degree of concentration in the transportation industry and of social interactions in cyberspace [39]. The Herfindahl-Hirschman index was introduced here to analyze the degree of business concentration in each port in a maritime network.…”
Section: Linkage Concentration Indexmentioning
confidence: 99%
“…The main directions for microblog data analysis are as follows: topic-event analysis (Ritter et.al, [14]; Yang et.al, [15]), sentiment analysis (Bollen et.al, [16]; Thewall et.al, [17]), information retrieval and recommendation (Spina et.al, [18]; Yao et.al, [19]), user network relation analysis (Recuero et.al,[20]; Yin et.al, [21]), information dissemination (Naaman et.al, [22]; Xue et.al, [23]), impact analysis (Ding et.al, [24]; Steeg and Galstyan, [25]), and analysis of intra-urban human mobility (Li et.al,[26]; Wu et.al, [27]). Li et al [9] constructed China's intercity geo-social network based on the relations among Sina Microblog (SM) users and revealed that China's intercity social network was substantially imbalanced with significant global heterogeneity and local heterogeneity. Zhen et al [4] analysed China's urban network hierarchy from the perspective of the microblog social network space and identified the centre cities of China's urban network and their clustering distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, social networks have integrated location-based services, which not only is more convenient for people to exchange information via social networks but also provides more methods for geography studies, such as the spatial structure of intercity information flow in virtual social networks, the relation system of urban spaces, spatial interaction mechanisms and urban spatial/temporal relationships. Social networks are critical for reconstructing and enriching theories of urban studies (Li et.al, [9]; Qin et.al, [10]) and can help social scientists reveal the mapping between the virtual cyberspace and the actual offline space, which compose the new organizational structure and activity patterns of human society (Yu and Shaw, [11]). …”
Section: Introductionmentioning
confidence: 99%